The Media Industry's Structural Transformation in Capitalism and the Role of the State: Media Economics in the Age of Digital Communication - Manfred Knoche (tripleC: Communication, Capitalism & Critique, 2016)
This paper discusses how the capitalist media industry has been structurally transformed in the age of digital communications. It takes an approach that is grounded in the Marxian critique of the political economy of the media. It draws a distinction between media capital, media-oriented capital, media infrastructure capital and media-external capital as the forms of capital in the media industry. The article identifies four capital strategies that media capital tends to use in order to try to maximise profits: a) The substitution of “old” by “new” media technology, b) the introduction of new transmission chan- nels for “old” media products, c) the definition of new property rights for media sectors and networks, d) the reduction of production and transaction costs. The drive to profit maximization is at the heart of the capitalist media industrys structural transformation. This work also discusses the tendency to the universalization of the media system in the digital age and the economic contradictions arising from it. It identifies activity fields of the media industrys structural transformation and shows how the concen- tration of the capitalist media markets is an essential, contradictory and inherent feature of the capital- ist media system and its structural transformation. The paper identifies six causes of why capital seeks to employ capital strategies that result in the me- dia industrys structural transformation. They include market saturation, overaccumulation, the tenden- cy of the profit rate to fall, capital-concentration, competition pressure, and advertising. The paper finally discusses the role of the state as an agent of capital in general and media capital in particular. It discusses the role of the state in privatisations, neoliberal deregulation, the formation of national com- petitive states, and various benefits that the state provides for media capital. This contribution shows that capital and capitalism are the main structural transformers of the media and communications system. For understanding these transformations, we need an approach that is grounded in Marxs critique of the political economy.
urn:nbn:at:at-ubs:3-3174
Keywords: 330; Medienökonomie; Kapitalismus; Medienindustrie; Digitalisierung; Transformation; Staat; Medienkonzentration; media economics; capitalism; media industry; transformation; state; mediaconcentration